Probiotics in Pain Regulation: Mechanisms and Evidence from Preclinical and Clinical Studies - Starovoitova, S.O.; Spivak, M.Ya.; Старовойтова, С.О.; Співак, М.Я. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Probiotics, postbiotics, and gut microbiota can influence in pain modulation, including: visceral pain, inflammatory pain, postoperative pain, neuropathic pain, osteoarthritis pain, musculoskeletal pain, complex regional pain syndrome, and fibromyalgia. Probiotics can increase the expression of cannabinoid and opioid receptors in colonic epithelial cells, which mediate analgesia and reduce hypersensitivity to pain stimuli. They modulate key immune signaling pathways and cytokine production. This immunomodulation leads to decreased pro-inflammatory cytokines and increased anti-inflammatory cytokines, reducing inflammation-induced pain. By improving the intestinal barrier function (e.g., enhancing tight junction proteins and mucin production) and competitively excluding pathogens, probiotics reduce gut permeability and inflammation, which can influence visceral pain perception. Certain probiotic strains produce neurotransmitters like serotonin, g-aminobutyric acid, and dopamine, which affect gut motility, mood, and pain signaling via the gut-brain axis. Bacterial proteases from probiotics can activate or inhibit protease-activated receptors on nerve terminals and epithelial cells, modulating nociceptor excitability and visceral pain. In osteoarthritis pain models, probiotics reduce expression of pain mediators in dorsal root ganglia and joint tissues, while increasing protective molecules like type II collagen and tissue inhibitor matrix metalloproteinase 1. Also, the gut microbiota plays a significant role in the pathophysiology of fibromyalgia syndrome, potentially influencing pain, mood, and sleep through the gut-brain axis. Postbiotics ameliorate bone loss in estrogen-deficient animal models by improving bone mineral content in the spine and femur, suggesting potential benefits for bone health and indirect relief of musculoskeletal pain. Research underscores the potential of probiotics as innovative analgesics with fewer side effects compared to conventional drugs, acting on pain-related receptors.